LONG-TERM CHANGES IN POLLUTION OF THE MARINE ENVIRONMENT IN THE SHOAL ZONE OF THE WESTERN PART OF THE NORTHERN CASPIAN SEA - G. M. Abdurakhmanov; A. F. Sokolsky; L. V. Boronina; G. B. Abuova; S. Z. Tazhieva; A. R. Salakhutdinova; N. I. Sokolskaya; E. A. Sokolskaya; N. V. Popova (Юг России: экология, развитие, 2014)
The provides long-term data от the state of the medium shallow waters west of the North Caspian.